TEACHER RECRUITMENT SYSTEM PRODUCTIVE BUILDING ENGINEERING EFFECTIVE IN VOCATIONAL SCHOOLS (A CASE STUDY OF SURAKARTA) - Solikhin, Solikhin; Thamrin, A G; Siswanto, Budi (Universitas Sebelas Maret, 2015)
The purpose of this research are to: (1) know procedure productive vocational teacher recruitment system gacor5000, (2) know advantage and drawbacks of the recruitment system, (3) Know system recruitment teachers productive SMK effective according to users and policy holders, (4) Knowing implementation associated with productive teacher recruitment system which is effective against lecture Profession Education in a study program at PTB. The research is a descriptive-qualitative with technique of data collection uses interview, observastion, and study document. The technique of data analysis use interactive model.Based on the result of research the study is the recruitment of teachers productive carried out through candidates. Excess recruitment system that is based on the condition of vocational and the ability of local. While the rest is distribution of teachers productive less evenly caused by the formation policy. Recruitment system teachers productive SMK effective according to users and policy holders by virtue of planning which includes the available budget and demand adapted to policy, based on bureaucratic and chain of command prevailing. Besides the implementation of the selection of using Computer Asissted Tes (CAT). The result of this research can be used as to the development of material lecture by making the draft / handouts / module that be integrated in a course called education professional , are useful to prepare college students study program PTB to become professional teachers. Keyword : Productive teacher recruitment, the procurement of the candidates, efective of recruitment, advantage and drawbacks of the selection of candidates,